At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

a) If [tex]\( A = \{x: x \leq 4, x \in \mathbb{N} \} \)[/tex] and [tex]\( B = \{x: x^2 - 5x - 6 = 0\} \)[/tex], find [tex]\( A \times B \)[/tex] and [tex]\( B \times A \)[/tex].

b) If [tex]\( P = \{2 \ \textless \ x \ \textless \ 7, x \in \mathbb{N} \} \)[/tex] and [tex]\( Q = \{x: x^2 = 3x\} \)[/tex], find [tex]\( P \times Q \)[/tex] and [tex]\( Q \times P \)[/tex].


Sagot :

Sure, let's solve each part step by step.

### Part A: Cartesian Products of Sets [tex]\( A \)[/tex] and [tex]\( B \)[/tex]

Step 1: Define Set [tex]\( A \)[/tex]

Given:
[tex]\[ A = \{ x \leq 4 \mid x \in \mathbb{N} \} \][/tex]
This means that [tex]\( A \)[/tex] contains all natural numbers [tex]\( x \)[/tex] such that [tex]\( x \leq 4 \)[/tex]. Thus:
[tex]\[ A = \{ 0, 1, 2, 3, 4 \} \][/tex]

Step 2: Define Set [tex]\( B \)[/tex]

Given:
[tex]\[ B = \{ x \mid x^2 - 5x - 6 = 0 \} \][/tex]
To solve for [tex]\( B \)[/tex], we must find the roots of the quadratic equation [tex]\( x^2 - 5x - 6 = 0 \)[/tex]. Factoring the quadratic equation, we get:
[tex]\[ (x - 6)(x + 1) = 0 \][/tex]
Hence, the solutions are:
[tex]\[ x = 3 \text{ and } x = -2 \][/tex]

So,
[tex]\[ B = \{ 3, -2 \} \][/tex]

Step 3: Find [tex]\( A \times B \)[/tex]

The Cartesian product [tex]\( A \times B \)[/tex] is the set of all possible ordered pairs [tex]\( (a, b) \)[/tex] where [tex]\( a \in A \)[/tex] and [tex]\( b \in B \)[/tex]. Thus:
[tex]\[ A \times B = \{ (a, b) \mid a \in A \text{ and } b \in B \} \][/tex]

Calculating the pairs:
[tex]\[ A \times B = \{ (0, 3), (0, -2), (1, 3), (1, -2), (2, 3), (2, -2), (3, 3), (3, -2), (4, 3), (4, -2) \} \][/tex]

Step 4: Find [tex]\( B \times A \)[/tex]

The Cartesian product [tex]\( B \times A \)[/tex] is the set of all possible ordered pairs [tex]\( (b, a) \)[/tex] where [tex]\( b \in B \)[/tex] and [tex]\( a \in A \)[/tex]. Thus:
[tex]\[ B \times A = \{ (b, a) \mid b \in B \text{ and } a \in A \} \][/tex]

Calculating the pairs:
[tex]\[ B \times A = \{ (3, 0), (3, 1), (3, 2), (3, 3), (3, 4), (-2, 0), (-2, 1), (-2, 2), (-2, 3), (-2, 4) \} \][/tex]

### Part B: Cartesian Products of Sets [tex]\( P \)[/tex] and [tex]\( Q \)[/tex]

Step 1: Define Set [tex]\( P \)[/tex]

Given:
[tex]\[ P = \{ x \mid 2 < x < 7 \text{ and } x \in \mathbb{N} \} \][/tex]
This means that [tex]\( P \)[/tex] contains all natural numbers [tex]\( x \)[/tex] such that [tex]\( 2 < x < 7 \)[/tex]. Thus:
[tex]\[ P = \{ 3, 4, 5, 6 \} \][/tex]

Step 2: Define Set [tex]\( Q \)[/tex]

Given:
[tex]\[ Q = \{ x \mid x^2 = 3x \} \][/tex]
To solve for [tex]\( Q \)[/tex], we need to find the roots of the equation [tex]\( x^2 - 3x = 0 \)[/tex]. Factoring the equation we get:
[tex]\[ x(x - 3) = 0 \][/tex]
Hence, the solutions are:
[tex]\[ x = 0 \text{ and } x = 3 \][/tex]

So,
[tex]\[ Q = \{ 0, 3 \} \][/tex]

Step 3: Find [tex]\( P \times Q \)[/tex]

The Cartesian product [tex]\( P \times Q \)[/tex] is the set of all possible ordered pairs [tex]\( (p, q) \)[/tex] where [tex]\( p \in P \)[/tex] and [tex]\( q \in Q \)[/tex]. Thus:
[tex]\[ P \times Q = \{ (p, q) \mid p \in P \text{ and } q \in Q \} \][/tex]

Calculating the pairs:
[tex]\[ P \times Q = \{ (3, 0), (3, 3), (4, 0), (4, 3), (5, 0), (5, 3), (6, 0), (6, 3) \} \][/tex]

Step 4: Find [tex]\( Q \times P \)[/tex]

The Cartesian product [tex]\( Q \times P \)[/tex] is the set of all possible ordered pairs [tex]\( (q, p) \)[/tex] where [tex]\( q \in Q \)[/tex] and [tex]\( p \in P \)[/tex]. Thus:
[tex]\[ Q \times P = \{ (q, p) \mid q \in Q \text{ and } p \in P \} \][/tex]

Calculating the pairs:
[tex]\[ Q \times P = \{ (0, 3), (0, 4), (0, 5), (0, 6), (3, 3), (3, 4), (3, 5), (3, 6) \} \][/tex]

### Summary of Results

- [tex]\( A \times B = \{ (0, 3), (0, -2), (1, 3), (1, -2), (2, 3), (2, -2), (3, 3), (3, -2), (4, 3), (4, -2) \} \)[/tex]
- [tex]\( B \times A = \{ (3, 0), (3, 1), (3, 2), (3, 3), (3, 4), (-2, 0), (-2, 1), (-2, 2), (-2, 3), (-2, 4) \} \)[/tex]
- [tex]\( P \times Q = \{ (3, 0), (3, 3), (4, 0), (4, 3), (5, 0), (5, 3), (6, 0), (6, 3) \} \)[/tex]
- [tex]\( Q \times P = \{ (0, 3), (0, 4), (0, 5), (0, 6), (3, 3), (3, 4), (3, 5), (3, 6) \} \)[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.